The great wall of confinement: the chinese prison camp through contemporary fiction and reportage - Williams, Philip F. (Univ. of California Press, 2004)
The cultural foundations of China's prison camp system -- The development of the Chinese communist prison camp -- The PRC prison camp (I) -- The PRC prison camp (II) -- Prison writings